A colônia penal feminina do Recife: um estudo sobre suas ocorrências no Jornal Diario de Pernambuco (1973- 1986). - Campos, Ricardo Sérgio de Souza (2024)
The present work aims to analyze the Recife Women's Penal Colony and its history, through the newspaper Diario de Pernambuco, between the years 1973 and 1986, resulting in the construction of an almanac, which will be distributed to the general public. During this period, prison reform took place in the State of Pernambuco, starting with the deactivation of the Recife detention house and the creation of new penitentiaries. As for incarcerated women, the place where the sentence of deprivation of liberty was served continued to be, during the period, the Recife Women's Penal Colony, located on Rua do Bom Pastor in the Engenho do Meio neighborhood. These prisoners were normally represented by an example of good conduct while serving their sentence. Thus, punishment was mixed with morality, as the so-called “reeducandes” had to avoid emotional involvement between them, in addition to the prohibition of receiving intimate visits. From the point of view of resocialization policy, there was also a defense of professional training for prisoners for domestic activities. We had authors such as Carlos Aguirre, Roger Chartier, Ângela Artur, Dário Melossi, Michel Foucault and Tânia de Luca as a theoretical foundation. The methodology will involve a critical analysis of incidents published in the newspaper Diario de Pernambuco.